Biomarker Assays for Personalised Stroke Risk Assessment in Atrial Fibrillation - Hall, Angela; F.G. Simpson, Rupert; R.J. Mitchell, Andrew (Cardiovascular & Haematological Disorders - Drug Targets, 2017)
Background: Atrial fibrillation is a well-known independent risk factor for stroke yet there is no international consensus on guidelines regarding the introduction of anticoagulation in patients deemed at intermediate risk (e.g. CHA2DS2-VASc of 1). The evolution of cardiac biomarkers such as highly sensitive troponins and B-type natriuretic peptide as well as data on D-dimers, may offer incremental enhancements for personalized thromboembolism risk assessment. These markers provide prognostic data for risk of cardiovascular morbidities associated with atrial fibrillation and offer additional specificity for assessing stroke and thromboembolic risk. These assays may therefore enhance risk prognosis in atrial fibrillation alongside conventional stroke risk stratification tool patients. We seek to explore the application of personalised risk assessment using the biomarkers to aid the clinician treating the patient with atrial fibrillation deemed to be at intermediate risk of stroke. Conclusion: The stroke risk assessment of a patient with an intermediate risk of stroke (CHA2DS2- VASc score 1) may be improved by using cardiac biomarkers such as highly sensitive troponin, BNP and D-dimers. We explore the application of these biomarkers to provide personalised risk assessment to help a patient with AF decide on whether to commence anticoagulation.
Keywords: personalised medicine